Contemporary India - Pachauri, R. K. (New Delhi : Vikash, 1992)
Contributed seminar papers.
"Under the auspices of Netaji Academy of Sub-Cntinental Studies."
Includes bibliographical references and index.
Keywords: Political parties -- India; India -- Politics and government -- 1977-; India -- Economic conditions -- 1947-; India -- Social conditions -- 1947-